COLLABORATIVE PAIR-INTERACTION: POSITIVE ROLE OF ZONE OF PROXIMAL DEVELOPMENT THEORY IN ESL CLASSROOMS - Wahyu Kyestiati Sumarno (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2016)
Although collaborative pair-interaction has shown as providing positive impacts on students’ second language learning, but none of studies has considered the important role of Zone of Proximal Development theory by Vygotsky in forming the pair and its effect during the pair-interaction. Zone of Proximal Development points out that adults and more competent peers can aid students’ development (Vygotsky in Tudge, 1990). Thus, in this study, the writer reviewed many literatures which investigated the nature of pair-interaction. Some of the studies showed that when the students were paired with both more and less competent partners, respectively, only students who were paired with more competent students got the benefit of the collaboration. Some of the research also noticed that regardless the students’ proficiency, the students will still learn as long as they can create collaborative pattern of interaction. From the above findings, it is suggested that for long-term teaching using collaborative pair-interaction, the theory of Zone of Proximal Development is necessary to be considered as a guideline in forming the students’ pair. Pairing intentionally is believed to be more beneficial in giving best environment for students’ learning, rather than randomly pairing the students all the time. Keywords: collaborative pair-interaction, zone of proximal development, ESL class